ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN, DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA DOSEN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi pada dosen Politeknik Negeri Sriwijaya) - Rini Rini; Heri Setiawan (Program Studi Magister Manajemen FE Unsri, 2010)
This research done in Polytechnic State of Sriwijaya and aimed at: finding the influence of Job Characteristic, individual characteristic, motivation on Lecturer Performance. This research used data that collected by survey with lecturer as respondent. Ninety five respondents were choosing as the samples by Stratified Random Sampling Method. Path Analyisis techniques were used to analyze data with use SPSS version 15.00 for windows. Job Characteristic, individual characteristic, as the independent variables (X), and Lecturer Performance as the dependent variables (Y). The results revealed that Job Characteristic has a significant effect on motivation. Perceived usefulness partially has a significant effect on computer self efficacy. Perceived ease of use partially has a significant effect on computer self efficacy. Attitude, perceived usefulness, perceived ease of use simultaneously have significant effect on computer self efficacy.Key words:Job Characteristic, Individual Characteristic, Motivation, Performance